Characteristics of Volume Reabsorption in Rabbit Superficial and Juxtamedullary Proximal Convoluted Tubules - Jacobson, Harry R. (1979)
Segments of superficial and juxtamedullary proximal convoluted tubules of the rabbit were perfused in vitro to examine the mechanisms responsible for net volume reabsorption. The very early postglomerular segments were not studied. Fluid reabsorptive rates and transepithelial potential differences were compared under various conditions: (a) with perfusate that simulated glomerular filtrate; (b) with perfusate that lacked glucose, amino acids, and acetate and that had HCO(3) and Cl concentrations of 5 and 140 mM, respectively; (c) with perfusate that lacked glucose, amino acids, and acetate but with 20 meq of NaHCO(3) replaced with 20 meq of Na cyclamate; (d) with the same perfusate as in b but in the presence of ouabain in the bath; (e) with ultrafiltrate of rabbit serum titrated with HCl to final HCO(3) and Cl concentrations of 2 and 134 mM, respectively. Tubules were perfused with this titrated ultrafiltrate at 37°C, 21°C, and in the presence of 0.1 mM ouabain in the bath. Bath fluid in all experiments was regular rabbit serum. Under conditions a and b superficial proximal convoluted tubule (SFPCT) and juxtamedullary proximal convoluted tubule (JMPCT) behaved similarly with the exception that SFPCT exhibited a lumen-positive and JMPCT a lumen-negative electrical potential under condition b. However, under condition c SFPCT failed to exhibit net volume reabsorption, whereas reabsorption in JMPCT continued unchanged. Ouabain did not affect volume reabsorption in SFPCT under condition d, whereas neither ouabain nor hypothermia affected SFPCT under condition e. In contrast, ouabain and hypothermia totally inhibited volume reabsorption in JMPCT under conditions d and e. These studies document heterogeneous mechanisms responsible for volume reabsorption in the major portions of SFPCT and JMPCT with passive forces predominating in SFPCT and active forces in JMPCT.